Characterization of an exopolysaccharide from probiont Enterobacter faecalis MSI12 and its effect on the disruption of Candida albicans biofilm1. Issue 88 (25th September 2015) - Kiran, G. Seghal; Priyadharshini, S.; Anitha, K.; Gnanamani, Elumalai; Selvin, Joseph
<x xml:space="preserve">Abstract</x> A study reporting the EPS from a probiotic strain Enterococcus faecalis MSI12 isolated from the marine environment and its potential as an antibiofilm agent and/or disruptor of pre-established biofilms of the most prominent human pathogen Candida albicans.